The effect of the war on human capital in Ukraine and the path for rebuilding - Yuriy Gorodnichenko; Marianna Kudlyak; Ayşegül Şahin (Institute of Labor Economics (IZA), 2022)
In February 2022, Russia launched a full-scale invasion of Ukraine. The ensuing war has a devastating destructing impact in Ukraine. This article focuses on the humanitarian cost of war. The article develops a framework for the analysis of the effect of a war on country's human capital. We then identify the following key directions for rebuilding and further developing human capital in Ukraine: quantity and quality of schooling for children, quality of higher education, training and retraining programs for adults, assistance for people with disabilities, post-deployment re-integration into the civilian sector, population growth and fertility, and promotion of self-motivating mechanisms.
Keywords: I2; J24; O4; 330; human capital; growth; schooling; skills of the future; health; war; displacement